The Role of Social Capital in Innovation and Performance: Evidence From Women Owned Smes in a Matrilineal Society - Games, Donard; Putri Ananda, Resky; Kurnia Sari, Dessy; Abbas, Asmi; Patrisia Komalasari, Sanda; Albatati, Bader Albatati (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
Women-owned small and medium-sized enterprises (SMEs) may have difficulties in establishing networks and business partnership. This is in particular because they may have limitations in building social interaction, which in turn enhances their entrepreneurial activities and business performance. However, this may differ in matrilineal such as Minangkabau, where women have privileges, including in business activities. They are inherited ancestral properties such as land and houses that can be seen as valuable assets in starting and developing businesses. Therefore, it is interesting to know whether women-owned SMEs in Minangkabau can benefit from social capital, more specifically, bridging social capital. This type of social capital signifies social interaction with weak ties or new people from new places. This paper aims to examine the relationships between social capital, innovation, and performance in the context of women-owned SMEs in Minangkabau. We employed a quantitative approach using smartPLS 4.0. Data were analyzed from 100 women-owned SMEs in Padang, the capital of West Sumatra. It was found that bridging social capital is significantly and positively related to innovation and performance. Additionally, innovation mediated the relationship between bridging social capital and women-owned SME performance. Accordingly, promoting bridging social capital and innovation to women-owned SMEs is an effective way to enhance business performance. This may confirm that women-owned SMEs need to expand their social interaction with new people and from new places. In this case, they can benefit from digital technology facilitating this and increase their degree of innovation.